Perlindungan data pribadi dan privasi di internet - Ahadia, Zahrotul (Maliki Interdisciplinary Journal, 2024)
Protecting personal data and privacy on the internet is becoming increasingly important as technology advances and digital interactions increase. Personal data includes information that can directly or indirectly identify an individual. The urgency of protecting personal data in the digital world arises because of the risk of misuse of data which can result in identity theft, fraud and privacy violations which can harm individuals. Personal data protection regulations have been implemented in various countries to regulate the collection, storage and processing of personal data, such as the Personal Data Protection Law in Indonesia. With strict regulations and law enforcement, it is hoped that the protection of personal data and privacy on the internet can be guaranteed, providing a sense of security for individuals when using digital technology.